2021
DOI: 10.1029/2020ms002346
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Chemistry‐Aerosol‐Climate Model CAM5‐Chem‐MAM7‐MOSAIC: Global Atmospheric Distribution and Radiative Effects of Nitrate Aerosol

Abstract: A modal version of the advanced aerosol chemistry module MOSAIC is developed and introduced in a climate model to simulate nitrate aerosol• MOSAIC provides an accurate and efficient treatment for dynamically partitioning semivolatile gases over to entire aerosol size distribution • The modeled global distribution of nitrate is in good agreement with observations and its impact on the radiative effects are quantified

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 89 publications
5
43
2
Order By: Relevance
“…Several novel methods (e.g., “dynamic pH” and “adaptive time stepping”) are used in MOSAIC to ensure accurate yet computationally efficient solutions. The first implementation of MOSAIC in a global climate and chemistry model was in the Community Atmosphere Model version 5, the atmosphere component, with chemistry (CAM5‐chem), of the Community Earth System Model version 1 (CESM1) and coupled with the 7‐mode version of the Modal Aerosol Module (MAM7) (Liu et al., 2012) and MOZART gas‐phase chemistry (Zaveri et al., 2021). In this study, we further implement the MOSAIC module in the 4‐mode version of the Modal Aerosol Module (MAM4) (Liu et al., 2016) in the CAM version 6 with chemistry (CAM6‐chem).…”
Section: Introductionmentioning
confidence: 99%
“…Several novel methods (e.g., “dynamic pH” and “adaptive time stepping”) are used in MOSAIC to ensure accurate yet computationally efficient solutions. The first implementation of MOSAIC in a global climate and chemistry model was in the Community Atmosphere Model version 5, the atmosphere component, with chemistry (CAM5‐chem), of the Community Earth System Model version 1 (CESM1) and coupled with the 7‐mode version of the Modal Aerosol Module (MAM7) (Liu et al., 2012) and MOZART gas‐phase chemistry (Zaveri et al., 2021). In this study, we further implement the MOSAIC module in the 4‐mode version of the Modal Aerosol Module (MAM4) (Liu et al., 2016) in the CAM version 6 with chemistry (CAM6‐chem).…”
Section: Introductionmentioning
confidence: 99%
“…The MOSAIC model is also widely used in regional and global chemical transport models, that is, the Weather, Research and Forecasting model with Chemistry (WRF-Chem) 50,51 and the Community Earth System Model (CESM). 52 We then applied the model to predict the particle size evolution and SOA composition upon IEPOX uptake by pure ammonium bisulfate particles from the chamber experiments reported in Riva et al 35 This work focuses on a single aerosol system, ammonium bisulfate seed aerosols under dry conditions (<5% RH).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this study, we integrated and applied new IEPOX-SOA modeling capabilities in a box model to understand kinetic processes governing evolution of particle size, chemical composition, and overall particle density due to reactive uptake of IEPOX, as measured by Riva et al The capability of a chemistry-aerosol inorganic box model, Model for Simulating Aerosols Interaction and Chemistry (MOSAIC), developed by Zaveri et al, was extended to include key processes of IEPOX-SOA formation on polydisperse aerosols. The MOSAIC model is also widely used in regional and global chemical transport models, that is, the Weather, Research and Forecasting model with Chemistry (WRF-Chem) , and the Community Earth System Model (CESM) . We then applied the model to predict the particle size evolution and SOA composition upon IEPOX uptake by pure ammonium bisulfate particles from the chamber experiments reported in Riva et al This work focuses on a single aerosol system, ammonium bisulfate seed aerosols under dry conditions (<5% RH).…”
Section: Introductionmentioning
confidence: 99%
“…Within the latest Coupled Model Intercomparison Project Phase 6 (CMIP6), the Scenario Model Intercomparison Project (ScenarioMIP) provides future projections of many climate variables based on state-of-the-art climate models with various emission scenarios and land use changes under the Shared Socioeconomic Pathways (SSPs). However, many of the CMIP6 models do not provide variables of aerosol components and chemical processes since they focus on future changes in climate rather than air quality. , Moreover, different aerosol components, such as nitrate, ammonium, and organic aerosols, are not fully represented in the majority of climate models, partly due to the consideration of the computational efficiency. , With available data, Turnock et al reported that PM 2.5 was underrepresented in the CMIP6 models over Asia, Europe, and North America. Some studies directly used emissions in the future scenarios as input to global chemical transport models, driven by present-day meteorological data, to project future aerosol changes. , This method does not take into account any impacts of climate change on aerosols through chemical, transport, and scavenging processes.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Moreover, different aerosol components, such as nitrate, ammonium, and organic aerosols, are not fully represented in the majority of climate models, partly due to the consideration of the computational efficiency. 20,21 With available data, Turnock et al 20 reported that PM 2.5 was underrepresented in the CMIP6 models over Asia, Europe, and North America. Some studies directly used emissions in the future scenarios as input to global chemical transport models, driven by present-day meteorological data, to project future aerosol changes.…”
Section: Introductionmentioning
confidence: 99%